Analysing the potential for modal shiftbased on the logic of modal choice. Issue 4 (2nd October 2022) - Bernier, Eloi; Kaufmann, Vincent; Masse, Florian; Gonzalez, Juliana
Abstract: This article explores how the logic underlying modal practices tends to modulate the population's responsiveness to improvements in global transport supply. Based on a quantitative survey conducted in 2018–2019 among the working population of the cantons of Bern, Geneva and Vaud, it presents the construction of eight types, each of which corresponds to a specific combination of action logic and allows segmentation of travel behaviour. The exploration of the links between this typology and three metropolitan areas shows that the weight of the types within the active population is associated with the quality of the transport offered, especially at the workplace, and that the use of the different means of transport for commuting within the types stays consistent with the opinions of the respondents, as confirmed by an ordinal regression. All the results presented in this article show that a modal shift objective in daily mobility requires a strategy that is segmented by these types.